AMDK Customer Satisfaction Analysis At Perumda Tirta Medal Sumedang - Sukmayadi Sukmayadi; Deno Hermawan (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
The occurrence of increasingly fierce competition in the Bottled Drinking Water (AMDK) industry, especially local products, makes customers prefer to choose products that suit their wants and needs. Perumda Tirta Medal Sumedang is a regional company engaged in the management, production and delivery of drinking water to the community that makes customer satisfaction its main priority. This research was conducted to determine customer satisfaction and efforts to increase customer satisfaction at Perumda Tirta Medal Sumedang using qualitative methods. The sampling technique used accidental sampling technique. Data obtained by the Miles and Huberman method through the process of data collection, data reduction, data presentation and drawing conclusions. The results of the research show that customer satisfaction at Perumda Tirta Medal Sumedang is already satisfied. This can be seen from the indicators of customer expectations which show that the products and services provided are as expected. Then the satisfaction seen from the indicator of interest in revisiting shows by providing services between products and providing the best service to customers, as well as the use of quality raw materials is considered quite satisfactory. Furthermore, satisfaction seen from visitors from the indicators recommend recommend also shows customers to recommend the AMDK Tirta Medal product to their relatives and friends because the service is considered good and the perceived benefits are very good for the health of the body because of the quality bottled drinking water.